Establishment of mouse Mac‐2 binding protein enzyme‐linked immunosorbent assay and its application for mouse chronic liver disease models. Issue 9 (13th October 2016) - Iwata, Ayumi; Kamada, Yoshihiro; Ebisutani, Yusuke; Yamamoto, Akiko; Ueda, Yui; Arai, Hitomi; Fujii, Hironobu; Takamatsu, Shinji; Maruyama, Nobuhiro; Maeda, Masahiro; Takehara, Tetsuo; Miyoshi, Eiji
Abstract: Aim: We identified Mac‐2 (galectin‐3) binding protein (Mac‐2bp) as a novel diagnostic and liver fibrosis predicting biomarker for nonalcoholic steatohepatitis in humans. In mouse models, there are no serum biomarkers predicting liver disease severity. In this study, we developed a mouse Mac‐2bp enzyme‐linked immunosorbent assay (ELISA) system and determined its efficacy for predicting the severity of liver disease in mouse models, especially in non‐alcoholic fatty liver disease (NAFLD) models. Methods: We established several rat monoclonal antibodies against mouse Mac‐2bp, selected two clones for the ELISA, and checked the accuracy and reproducibility of the ELISA, especially for NAFLD models and liver fibrosis models. We also investigated the relationships between serum levels and hepatic gene expression of Mac‐2bp in mouse models. Results: Our ELISA system had high accuracy and reproducibility (R 2  = 0.999). The intra‐assay and inter‐assay results for the coefficient of variation were 2.0–3.7% and 1.7–6.9%, respectively. The levels of bilirubin, hemoglobin, and chyle did not affect the Mac‐2bp serum levels detected by our ELISA kit. In the mouse models, serum Mac‐2bp levels increased with liver disease progression (F0/F1/F2/F3, 239.1 ± 36.7 / 259.1 ± 43.0 / 457.5 ± 162.0 / 643.7 ± 116.0 ng/mL; P  < 0.0001), and were significantly correlated with hepatic gene expression of Mac‐2bp ( R  = 0.42, P  < 0.0001). Conclusion: Our mouse Mac‐2bp ELISA system effectively predicts severity of NAFLD and liver fibrosis in mouse models.